Hydrolysed wheat based oral rehydration solution for acute diarrhoea. Issue 5 (May 1987) - Alam, A N; Sarker, S A; Molla, A M; Rahaman, M M; Greenough, W B
Abstract : A randomised three cell study was carried out in 78 children with acute diarrhoea to evaluate the relative efficacy of oral rehydration solution (ORS) made from partially hydrolysed wheat grain, cooked rice powder, or glucose. Twenty six patients with comparable age, body weight, duration of diarrhoea, and degree of dehydration were studied in each of the three groups. Initial rehydration was carried out by using intravenous Dhaka solution within one to two hours followed by administration of oral rehydration solution. The mean ORS intake during the first and second 24 hours of treatment in patients with cholera receiving wheat-ORS and rice-ORS was significantly less compared with those receiving glucose-ORS. The stool output during the same period in patients receiving wheat-ORS and rice-ORS was significantly less compared with those receiving glucose-ORS. Similar trends in both ORS intake and stool output were observed during the next 24 hours.